Faith as politics-and politics as faith: Beyers Naudé and Dag Hammarskjöld - Melber, Henning (Faculty of the Humanities, University of the Free State, 2015)
This essay explores commonalities in the faith and political spirituality of Dag Hammarskjöld (1905-1961) and Beyers Naudé (1915-2004) on occasion of the hundredth birthday of “Oom Bey”, as Beyers Naudé was called by those who knew him well. It presents the theology of Naudé and the spiritual dimensions of Hammarskjöld in the context of political engagement taking forms of empathy and commitment towards social justice and respect for otherness. Using their statements, it shows the parallels in their thinking, which understood faith as politics and, at the same time, politics as a matter of faith. Thereby, this essay suggests that, despite their different roles as pastor in South Africa and as Secretary General of the United Nations (UN) during the times of decolonization on the African continent respectively, both converged to a large extent in the values motivating their active roles played also in the political arena of their times
Keywords: Beyers Naudé; Dag Hammerskjöld; Faith; Spirituality; Politics; Solidarity; Apartheid; United Nations (UN)